Subtract 1111 from both sides
5{e}^{{4}^{x}}=22-115e4x=22−11
Simplify 22-1122−11 to 1111
5{e}^{{4}^{x}}=115e4x=11
Divide both sides by 55
{e}^{{4}^{x}}=\frac{11}{5}e4x=511
Use Definition of Natural Logarithm: {e}^{y}=xey=x if and only if \ln{x}=ylnx=y
{4}^{x}=\ln{\frac{11}{5}}4x=ln511
: {b}^{a}=xba=x if and only if log_b(x)=alogb(x)=a
x=\log_{4}{\ln{\frac{11}{5}}}x=log4ln511
Use Change of Base Rule: \log_{b}{x}=\frac{\log_{a}{x}}{\log_{a}{b}}logbx=logablogax
x=\frac{\log{\ln{\frac{11}{5}}}}{\log{4}}x=log4logln511
Use Power Rule: \log_{b}{{x}^{c}}=c\log_{b}{x}logbxc=clogbx
\log{4}log4 -> \log{{2}^{2}}log22 -> 2\log{2}2log2
x=\frac{\log{\ln{\frac{11}{5}}}}{2\log{2}}x=2log2
Answer= −0.171
You multiply the number outside the parenthesis with both of the numbers in the parenthesis separately.
Answer:
yes 48 3/5
Step-by-step explanation:
Answer:
(y times 6) -1
Step-by-step explanation:
I don't know what to say it is already simplified
Answer:
Step-by-step explanation:
To find f(a), replace x with a: f(a)=6−1a+15a^2
To find f(a+h), replace x with (a+h): f(a+h) = 6 -(a + h) + 15(a+h)^2
To find f(a+h)−f(a), expand f(a+h) as given above, and then subtract f(a):
f(a+h)−f(a) = 6 -a - h + 15(a^2 + 2ah + h^2) - [6 - a + 15a^2]
6 - a - h + 15a^2 + 30ah + 15h^2 - [6 - a + 15a^2]
This simplifies to: f(a+h)−f(a) = - h + 30ah + 15h^2